IMPROVING STUDENTS™ ACHIEVEMENT IN VOCABULARY BY USING FLASHCARD - Marpaung, Amalia; Zainuddin, Zainuddin (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study concerned on improving students ˜achievement in vocabulary by using flashcard. The objective of this study was to found out the improvement of students™ achievement in vocabulary by using flashcard. This research was conducted by using action research method. The subject of the study was VII-4 student of SMA Prayatna Medan, which consisted of 30 students. The instruments of collecting data were quantitative (vocabulary test) and qualitative data (diary notes, and observation sheets). In analyzing, the mean of students™ score for the first vocabulary test was 40.33 the second vocabulary was 64 and the third vocabulary test was 83. The total percentage of the improvement from the first vocabulary test to the third was 100%.The conclusion is the application of flashcard can improve students™ achievement in vocabulary. The qualitative data show that students were enthusiastic and interested in learning vocabulary during the teaching learning process.   Keywords: Achievement, vocabulary, flashcard